2013
DOI: 10.1155/2013/834704
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty-Aware Sensor Deployment Strategy in Mixed Wireless Sensor Networks

Abstract: Deployment is a fundamental issue in wireless sensor networks (WSNs), which affects the performance and lifetime of the networks. Usually the sensor locations are precomputed based on "perfect" sensor detection model, whereas sensors may not always provide reliable information, either due to operational tolerance levels or environmental factors. Therefore, it is very important to take into account this uncertainty in the deployment process. In this paper, we address the problem of sensor deployment in a mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although random deployment has been considered yet, the presence of obstacles in the field of interest has not been realized. Uncertainty Aware Deployment Technique (UADT) has been evaluated using detection probability and connectivity percentage in mixed wireless sensor networks [20]. In particular, authors have suggested a deployment approach which discovers coverage holes by computing joint detection probability and moves the appropriate mobile sensors into coverage holes using bipartite graph based approach.…”
Section: B Double Metrics Based Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although random deployment has been considered yet, the presence of obstacles in the field of interest has not been realized. Uncertainty Aware Deployment Technique (UADT) has been evaluated using detection probability and connectivity percentage in mixed wireless sensor networks [20]. In particular, authors have suggested a deployment approach which discovers coverage holes by computing joint detection probability and moves the appropriate mobile sensors into coverage holes using bipartite graph based approach.…”
Section: B Double Metrics Based Measurementmentioning
confidence: 99%
“…Therefore, qualitative measurements of these geometrical model based deployment patterns for precision agriculture use case of WSNs need to be investigated considering the early stage development in precision agriculture use case of WSNs [9,12]. Further, most of these geometrical model-based deployment patterns have been evaluated using single [13][14][15][16] or double [17][18][19][20] metrics of coverage and connectivity. In real applications, performance of these geometrical model-based deployment patterns are quite different and far away from the reported performance in literature which are based on evaluations considering single or double metrics of coverage and connectivity [21].…”
mentioning
confidence: 99%
“…While, the dynamic deployment methods are mainly used in a mobile WSNs (i.e. the sensor node has mobility) [3], after being scattered in AOI, the sensor nodes accomplish deployment autonomously. The autonomous deployment of mobile WSNs is a process in which the mobile sensor nodes adjust their positions dynamically according to a certain algorithm.…”
Section: Introductionmentioning
confidence: 99%